Knowledge, Attitude, and Practice of Vitamin D Intake Among Pregnant Women in Calabar: Implications for Maternity Care in the Tropics - Eyong E; Omoronyia EE; Eyong M; Ekpe L; Ikobah J; Odusolu P (Ibom Medical Journal)
Background: Vitamin D is a micronutrient essential for calcium and phosphorus homeostasis. It is required for optimal maternal health, fetal skeletal development, bone formation and good immune function. Though the vitamin is present in many locally available foods, as well as through supplementation and exposure to sunshine, these practices may require adequate knowledge and a good attitude towards vitamin D by pregnant women. This study aimed to assess these parameters among pregnant women in a tropical developing country setting with adequate daily sunshine.